2022
DOI: 10.1080/21645515.2022.2138047
|View full text |Cite
|
Sign up to set email alerts
|

Models of determinants of COVID-19 vaccine hesitancy in non-pregnant and pregnant population: Review of current literature”

Abstract: Vaccination has proven to be the most effective tool in controlling the COVID-19 pandemic. While pregnant individuals are considered to be a high-risk population and are more likely to experience adverse effects from COVID-19, vaccination rates among pregnant individuals are significantly lower than in the general population. The Health Belief Model (HBM), Theory of Planned Behavior (TPB), 3C model, 5C model, and 5A model have been used to assess vaccination hesitancy behaviors. In this paper, we review the us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 151 publications
3
22
0
Order By: Relevance
“…At the same time, we need to summarize the main reasons for each Weibo in the expressed vaccine hesitancy based on the output keyword results and the definition of the 5C model. In this study, confidence indicates users’ confidence in the COVID-19 vaccine, government, medical organizations, and vaccine development organizations; complacency indicates users’ contempt for Covid risk; constraints indicate users’ vaccination behavior is limited by their own psychological or physical conditions; calculation indicates the user’s search for and knowledge of vaccine information and the judgment of vaccination necessity obtained through information evaluation; and collective responsibility indicates the user’s willingness to protect others or promote herd immunity through vaccination [ 25 , 26 , 27 ]. The specific operations are as follows.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, we need to summarize the main reasons for each Weibo in the expressed vaccine hesitancy based on the output keyword results and the definition of the 5C model. In this study, confidence indicates users’ confidence in the COVID-19 vaccine, government, medical organizations, and vaccine development organizations; complacency indicates users’ contempt for Covid risk; constraints indicate users’ vaccination behavior is limited by their own psychological or physical conditions; calculation indicates the user’s search for and knowledge of vaccine information and the judgment of vaccination necessity obtained through information evaluation; and collective responsibility indicates the user’s willingness to protect others or promote herd immunity through vaccination [ 25 , 26 , 27 ]. The specific operations are as follows.…”
Section: Methodsmentioning
confidence: 99%
“…Confidence (confidence in vaccines, healthcare workers, policymakers), complacency (not perceiving diseases as high risk), constraints (structural and psychological barriers), the calculation (engagements in extensive information searching), and collective responsibility (willingness to protect others) [ 24 ]. Tostrud et al [ 25 ] argue that the 5C model is comprehensive in considering vaccine hesitancy causes. It can better match the complex information environment of social media and has also achieved good results in examining COVID-19 vaccine hesitancy [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…There is a paucity of information on the perception of pregnant women about COVID-19 vaccination programmes, particularly among low-income countries and, especially, those in the sub-Saharan African (SSA) region. Considering the low uptake of COVID-19 vaccines among pregnant women, previous findings from a review study suggested different strategies to increase vaccination among pregnant individuals, including promoting evidence-based information on vaccine safety among pregnant women [ 26 ]. Therefore, the present study was designed to evaluate the acceptance and risk perception of pregnant and non pregnant women towards COVID-19 vaccines using a cross-sectional matched-sample study approach.…”
Section: Introductionmentioning
confidence: 99%
“…First of all, the present study had a cross-sectional design: by definition, cross-sectional studies have no dimension of time, so they cannot support conclusions on the risk factors of the targeted outcome, nor on causal relationships [ 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 ]. Without a well-defined dimension of time, cross-sectional studies can be poorly suited for examining conditions of short duration [ 92 , 93 , 94 ]: from this point of view, a cross-sectional design may be well suited for studying the acceptance of vaccine interventions [ 65 , 95 ], as the research would inquire about the overall status of the targeted individuals before the intervention [ 83 , 96 , 97 ], while retrieved information on infectious diseases and associated risk factors should be more cautiously assessed [ 94 , 95 , 98 ].…”
Section: Discussionmentioning
confidence: 99%